Comparison of performance between national bank and private bank on customers in Indonesia - Hazell Ikhsan Adri; Joshua Supriyanto; Luh Putu Cantika Kumara Tungga Adistri; Muhammad Adzka Labieb; Muhammad Ivanka; Naufal Fathurrahman Danang; Puti Maharani Keiva; Raihan Fadillah (Priviet Social Sciences Journal, 2021)
There are two types of banks in Indonesia, namely state-owned banks or national banks and private banks. The two banks have different orientations. The difference can be seen from the source of the funds they get. In this case, the National Bank usually gets larger funds from the private sector from government subsidies. Behind the statement regarding banking, we must know the performance of several banks in Indonesia, both national banks and private banks. As it is known that the performance of banks towards customers in recent years has been volatile, that the performance of banks in Indonesia has experienced several declines and increases. the results obtained that the performance of private banks is considered better than the national bank, this is supported by the results of the Sum of Rank which shows the number 1928.00 which has a greater value than that of the National Bank which is worth 998.00 and it is shown that there is a value of N positive ranks. of 43 which is greater than the value of N negative ranks of 33. Therefore, it can be concluded that the performance of private banks is greater than that of national banks. It can be concluded that the comparison between National Banks and Private Banks has an important role in gaining trust and gaining a good image among the public.